The impact of microburst-induced load variations on aircraft performance through numerical simulation - Ali Pourmoradi; Mehdi Sabzehparvar (Scientific Reports)
Abstract Microburst is a meteorological occurrence that presents a significant and inescapable hazard to aircraft during the critical phases of takeoff and landing. The investigation focused on the aircraft’s dynamic response to microburst phenomena. It is essential to conduct further research on the interplay between microbursts and aircraft movement to evaluate the implications of aerodynamic forces and momentum on flight performance. The multi-point loading approach offers a significant advantage over traditional integrated aerodynamic models utilized in recent research, as it enables the assessment of microburst wind loading at any specific location on the wing and tail configuration. In this approach, a comprehensive reconstruction of aerodynamic forces and moments is achieved through the integration of microbursts, utilizing various non-uniformly distributed load functions applied to each surface of the aircraft. This algorithm addresses the equations governing the motion of an aircraft possessing six degrees of freedom, while simultaneously updating the dynamic parameters of the aircraft. This process facilitates the computation of microburst effects that vary with both time and space for each individual element. In light of the unavailability of adequate experimental data, the method was assessed through a validated numerical simulation. Consequently, validation was conducted utilizing computational fluid dynamics (CFD) analysis at various intervals throughout the flight. The findings indicate that the present investigation has been validated with a satisfactory level of precision. Ultimately, we conduct simulations and juxtapose the outcomes of both multi-point and single-point methodologies, revealing notable disparities in flight parameters, including aircraft airspeed, angle of attack, and sideslip angle.